Effectiveness of oral irrigation with an extract of green microalga Nannochloropsis oculata as an anti-inflammatory in rats infected with Aggregatibacter actinomycetemcomitans - SYAMSULINA REVIANTI; DWI ANDRIANI; KRISTANTI PARISIHNI; ENDAH WAHJUNINGSIH; WIDYASTUTI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Revianti S, Andriani D, Parisihni K, Wahjuningsih E, Widyastuti. 2020. Effectiveness of oral irrigation with an extract of green microalga Nannochloropsis oculata as an anti-inflammatory in rats infected with Aggregatibacter actinomycetemcomitans. Biodiversitas 21: 2977-2981. Aggressive periodontitis is strongly correlated with Aggregatibacter actinomycetemcomitans, a periodontopathic bacterium, which releases endotoxins and lipopolysaccharides (LPS). LPS acts as a stimulus to a variety of host cells that can promote the expression of pro-inflammatory cytokines, such as the tumor necrosis factor-? (TNF-?), in periodontal disease. The marine green microalga Nannochloropsis oculata has anti-inflammatory properties. This study aimed to examine the anti-inflammatory efficacy of oral irrigation with N. oculata extract against periodontitis induced by A. actinomycetemcomitans in a rat model. Twenty-four male Wistar rats were divided randomly into four groups (n = 6). First control group was without any treatment, the second to fourth groups were infected with A. actinomycetemcomitans and then orally irrigated with N. oculata extract at concentrations of 2.375%, 2.5%, and 2.625%. The mandibles of the euthanized rats were hemisected to measure the expression of TNF-?, interleukin-10 (IL-10, an anti-inflammatory cytokine), and osteoprotegerin (OPG) by immunohistochemistry. The first group (control) showed significantly higher expression of TNF-? and significantly lower expression of IL-10 and OPG compared to the other groups. Oral irrigation with N. oculata extracts reduced the expression of TNF-? and enhanced the expression of IL-10 and OPG in rats infected with A. actinomycetemcomitans. The effective concentration of N. oculata extract as an anti-inflammatory for oral irrigation was 2.375%.